A National Process to Enhance the Validity of Entrustment Decisions for Dutch Pediatric Residents - Smit, Maaike P. (J Grad Med Educ, 2019)
BACKGROUND: Postgraduate medical education (PGME) has become increasingly individualized, and entrustable professional activities (EPAs) have been adopted to operationalize this. At the same time, the process and content to determine residents' progress using high-stakes summative entrustment decisions by clinical competency committees (CCCs) is not yet well established. OBJECTIVE: We evaluated the experiences with a structured process for assessment of EPAs to attain uniform summative entrustment decisions for a national sample of pediatric residents. METHODS: An EPA-based national PGME program for pediatric residents was introduced in the Netherlands, including a process of uniform summative entrustment decisions, termed the Evaluation and Assessment of Residents by Supervisors (EARS) procedure. To evaluate the program, we assessed survey data and information from invitational conferences. RESULTS: Beginning in January 2017, 125 pediatric residents in all 8 Dutch residency regions started training in the EARS program. The program enabled robust summative entrustment decisions. Preliminary data suggested that faculty, despite increased preparation time, appreciated the comprehensive appraisal of resident qualifications. The EPA-based program was well accepted by residents. Fifty-one percent (57 of 112) had at least 2 EARS procedures per year, and for 75% (84 of 112) the level of supervision was often or always adjusted to their level of training. CONCLUSIONS: A national EPA-based program provided a structured process for summative entrustment decisions by CCCs and enabled individualized stepwise progression of residents toward unsupervised practice. Broader application of these concepts may require adaptations to accommodate different health care systems and specialties.